2013
DOI: 10.1111/lam.12091
|View full text |Cite
|
Sign up to set email alerts
|

The antimicrobial effects of helium and helium–air plasma on Staphylococcus aureus and Clostridium difficile

Abstract: Significance and Impact of the Study: Many bacterial causes of healthcare infection can survive in the inanimate environment for lengthy periods and be transmitted to patients. Furthermore, current methods of environmental decontamination such as detergents, chemical disinfectants or gaseous fumigation are suboptimal for a variety of reasons. We assessed the efficacy of helium and helium-air plasma as a decontaminant and demonstrated a significant reduction in bacterial counts of Staphylococcus aureus on a gla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 17 publications
(28 reference statements)
1
15
0
Order By: Relevance
“…This fungicidal property of NTP also suggests its usefulness in decontaminating animal farms. The antibacterial efficacy of NTP has been further confirmed by several groups (4,30,(38)(39)(40). NTP has been found to have antibacterial effects on a variety of bacteria (41,42), on ESKAPE pathogens in the environment (17), on multi-drugresistant bacteria in surface environments (43).…”
Section: High-touch and Frequently-touched Surfaces And Instruments Cmentioning
confidence: 88%
See 1 more Smart Citation
“…This fungicidal property of NTP also suggests its usefulness in decontaminating animal farms. The antibacterial efficacy of NTP has been further confirmed by several groups (4,30,(38)(39)(40). NTP has been found to have antibacterial effects on a variety of bacteria (41,42), on ESKAPE pathogens in the environment (17), on multi-drugresistant bacteria in surface environments (43).…”
Section: High-touch and Frequently-touched Surfaces And Instruments Cmentioning
confidence: 88%
“…To date, NTP has been identified as an effective, low-cost and non-toxic way to decontaminate surfaces, instruments and confined environments (15,16,29). It has been shown that NTP produced from single-jet system eradicates vegetative bacteria from different surfaces (16,30) and NTP from multi-jet system is capable of reducing surface pathogens such as methicillin-resistant staphylococcus aureus, Clostridium difficile, Escherichia coli, Pseudomonas aeruginosa, Klebsiella pneumoniae and Acinetobacter baumannii (16). Furthermore, other studies have also demonstrated the successful decontamination of surfaces and instruments from these pathogenic organisms by NTP treatment (6,15).…”
Section: High-touch and Frequently-touched Surfaces And Instruments Cmentioning
confidence: 99%
“…All of these tests were completed on cells air-dried on glass slides. 87 To evaluate the efficacy of a CAPP, however, we selected surface materials routinely found in the clinical environment, including marmoleum flooring, polyurethane mattress fabric, polypropylene plastic, powdercoated mild steel, and stainless steel. All surfaces were inoculated with MRSA, ESBL E. coli, vancomycin-resistant Enterococcus faecalis, and Acinetobacter baumannii and treated for periods of 30, 60, and 90 s. The optimum antimicrobial activity of the air plasma in this study was observed after 90 s, producing reductions of 3e5 log 10 for MRSA, 2e5 log 10 for VRE, 2e3 log 10 for E. coli and 1.7e3 log 10 for A. baumannii, all of which were air-dried on each test surface.…”
Section: Applications Of Capp In Decontaminationmentioning
confidence: 99%
“…C. difficile colonization increases with the length of hospital stay following environmental exposure to spores or contact with an infected person (3). Contamination and survival of C. difficile spores on hospital inanimate surfaces have been reported (4, 5) and shown to be associated with cross-transmission (6-8).Inactivation and eradication of Clostridium difficile spores are a challenge, and several relatively new techniques have been investigated, such as hydrogen peroxide vapor, UV radiation, or gaseous plasma systems (5,6,9,10). Validation of such techniques should use optimal recovery methods to better quantify bacterial spore killing or eradication.…”
mentioning
confidence: 99%
“…Inactivation and eradication of Clostridium difficile spores are a challenge, and several relatively new techniques have been investigated, such as hydrogen peroxide vapor, UV radiation, or gaseous plasma systems (5,6,9,10). Validation of such techniques should use optimal recovery methods to better quantify bacterial spore killing or eradication.…”
mentioning
confidence: 99%